Structural analysis of some heterocyclic analogues (Chalcone, pyrazoline, ester and xanthone) and evaluation of their biological potentials - Loh, Wan Sin (2016)
In this research, four senes of a total of 33 compounds consisting of chalcone, pyrazoline, phthalimide ester and xanthone heterocyclic analogues were synthesized and were crystallized. Their molecular structures were elucidated by Xray diffraction method, using either Bruker SMART APEX II or Bruker APEX II DUO CCD area-detector diffractometers. It revealed the importance ofsubstituents on the crystal stability and molecular packing. Subsequently, they were screened for their biological potentials such as antioxidants, antimicrobial and anticancer. Chalcone derivatives showed mild to good antioxidant ability. Among them derivatives with methoxy substituents (-OCH3) at their phenyl rings exhibited the highest antioxidant activity. Chalcone with halogen sub tituents were te ted for antimicrobial activity and were found that fluoro substituent at -para po ition of the phenyl ring showed elevated antimicrobial activity. Pyrazoline derivatives displayed insignificant activity towards antioxidant and antimicrobial activitie . Phthalimide ester derivatives were evaluated for their in-vitro antioxidant properties